2019
DOI: 10.1016/j.fertnstert.2019.09.037
|View full text |Cite
|
Sign up to set email alerts
|

Short- and long-term impact of gonadotropin-releasing hormone analogue treatment on bone loss and fracture

Abstract: Gonadotropin-releasing hormone analogues (GnRH-a) are commonly utilized in moderate to severe endometriosis to induce atrophy of endometriotic lesions. Unfortunately, cessation of therapy can lead to recurrence of symptoms. Therefore, long term therapy is sometimes necessary. GnRH analogues cause an immediate decrease in bone mineral density which usually recovers after cessation of its use. However, this recovery in bone mineral density may not always occur after long term use. In order to prevent the deleter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 33 publications
0
37
0
Order By: Relevance
“…56 To mitigate the hypoestrogenic effects of GnRH agonists, including reductions in BMD, they may be administered in conjunction with add-back therapy to restore estrogen to a level at which bone loss is prevented but endometrial tissue is not stimulated. 11 Data from meta-analyses 57,58 and recent studies 59,60 confirm that add-back therapy mitigates bone loss associated with GnRH agonist treatment.…”
Section: Gnrh Agonistsmentioning
confidence: 91%
See 3 more Smart Citations
“…56 To mitigate the hypoestrogenic effects of GnRH agonists, including reductions in BMD, they may be administered in conjunction with add-back therapy to restore estrogen to a level at which bone loss is prevented but endometrial tissue is not stimulated. 11 Data from meta-analyses 57,58 and recent studies 59,60 confirm that add-back therapy mitigates bone loss associated with GnRH agonist treatment.…”
Section: Gnrh Agonistsmentioning
confidence: 91%
“…GnRH agonists are used in the treatment of multiple conditions affecting premenopausal women, including endometriosis, uterine fibroids, and adenomyosis, as well as for fertility preservation. 11 After an initial flare of pituitary gonadotrophs, GnRH agonist administration profoundly reduces luteinizing hormone and follicle-stimulating hormone levels, thereby suppressing estrogen and progesterone production. This mechanism of action induces maximum ovarian suppression, with associated side effects that include decreases in BMD.…”
Section: Gnrh Agonistsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have revealed that women with endometriosis did not exhibit a decrease in BMD compared to women of the same age without endometriosis [18,19], and that long-term fracture risks did not increase in women with endometriosis [20]. Meanwhile, regarding the decrease in BMD as a side effect of hormone therapy, the impact of add-back therapy using gonadotropin-release hormone analogues and oestrogen preparations for bone protection [21], as well as the decrease in BMD due to long-term administration of Dienogest, a progestin preparation [22] have been investigated. Another report suggested that BMD was higher after ovariectomy for deep endometriosis than after ovariectomy for other indications [23].…”
Section: Introductionmentioning
confidence: 99%